Comparative Morpho-Meristic Variations of Asian Stinging Catfish (Heteropneustes Fossilis) Collected from Natural and Hatchery Sources in Bangladesh (Bangladesh Journal of Zoology, 2025)
The present study sought to differentiate various sources of Heteropneustes fossilis samples morphologically using two hundred and twenty-five samples from six natural and three hatchery sources in Bangladesh. Eighteen morphometric and five meristic characters were studied, and the analysis highlighted that natural stocks were significantly different from hatchery stocks. The multivariate analysis showed a significant difference (p